Pup1 QTL Regulates Gene Expression Through Epigenetic Modification of DNA Under Phosphate Starvation Stress in Rice - Kumar, Suresh; Seem, Karishma; Kumar, Santosh; Vinod, K. K.; Chinnusamy, Viswanathan; Mohapatra, Trilochan (Frontiers in Plant Science, 2022)
Cytosine methylation, epigenetic DNA modification, is well-known to regulate gene expression. Among the epigenetic modifications, 5-methylcytosine (5-mC) has been one of the extensively studied epigenetic changes responsible for regulating gene expression in animals and plants. Though a dramatic change in 5-mC content is observed at the genome level, the variation in gene expression is generally less than it is expected. Only a little is understood about the significance of 5-mC in gene regulation under P-starvation stress in plants. Using whole-genome bisulfite sequencing of a pair of rice [Pusa-44 and its Near Isogenic Line (NIL)-23 harboring Pup1 QTL] genotypes, we could decipher the role of Pup1 on DNA (de)methylation-mediated regulation of gene expression under P-starvation stress. We observed 1315% of total cytosines to be methylated in the rice genome, which increased significantly under the stress. The number of differentially methylated regions (DMRs) for hypomethylation (6068) was higher than those (5279) for hypermethylated DMRs under the stress, particularly in root of NIL-23. Hypomethylation in CHH context caused up-regulated expression of 489 genes in shoot and 382 genes in root of NIL-23 under the stress, wherein 387 genes in shoot and 240 genes in root were up-regulated exclusively in NIL-23. Many of the genes for DNA methylation, a few for DNA demethylation and RNA-directed DNA methylation were up-regulated in root of NIL-23 under the stress. Methylation/demethylation of DNA in genic regions differentially affected gene expression. Correlation analysis for the distribution of DMRs and gene expression indicated regulation of gene mainly through (de)methylation of promoter. Many of the P-responsive genes were hypomethylated/up-regulated in roots of NIL-23 under the stress. Hypermethylation of gene-body in CG, CHG, and CHH contexts caused up-/down-regulated expression of transcription factors (TFs), P transporters, phosphoesterases, retrotransposon and other proteins. Our integrated transcriptome and methylome analysis revealed important role of the Pup1 QTL in epigenetic regulation of the genes for transporters, TFs, phosphatases, carbohydrate metabolism, hormone-signaling, and chromatin architecture/epigenetic modifications in P-starvation tolerance. This provides insights into the molecular function of Pup1 in modulating gene expression through DNA (de)methylation, which might be useful in improving P-use efficiency/productivity of rice in P-deficient soil.